CHILDREN'S EDUCATION ACCORDING TO ABDULLAH NASHIH ULWAN AND ITS IMPLEMENTATION IN CHILDREN'S EDUCATION IN FAMILY IN RT 02 / RW 012 LUBUK BUAYA KOTO TANGAH - puspita aryanti (Program Pascasarjana UMSB, 2022)
This research was conducted to describe how the concept of education carried out by parents in one RT in Lubuk Buaya Koto Tangah. Given that in the era of globalization and the rapid development of science and technology now, it turns out that many have positive and negative influences on society both in ways of thinking, acting and behaving, so we need a concept and theory that can be implemented in educating children from an early age. This research was conducted in RT 02 / RW 012 Lubuk Buaya Koto Tangah. The purpose of this study is to describe the education of children according to Abdullah Nashih Ulwan through the development of faith, worship, and morals, and their implementation in the education of children in the family in RT 02 / RW 012 Lubuk Buaya Koto Tangah. The results of this study reveal that: (1) Children's education in the family in RT 02 / RW 012 Lubuk Buaya Koto Tangah by opening the child's life with the sentence Tauhid Lailahaillallah, teaching him halal and haram issues after he is mature (baligh), ordering him to worship when he is old seven years, and educated him to love the Prophet, his family and to read the Qur'an. and introduce and explain to children about the pillars of faith. Apart from that, according to this method, it is also carried out through the pillars of faith and the pillars of Islam. (2) The education of children in the family in RT 02 / RW 012 Lubuk Buaya Koto Tangah is through various methods such as habituation, punishment, advice, attention, and example. In fact, parents have familiarized and taught children to pray on time, invite children to pray to the mosque, fast, teach about Hajj, and zakat and alms. (3) The education of children in the family in RT 02 / RW 012 Lubuk Buaya Koto Tangah is that parents foster their children's morals according to the advice of Abdullah Nashih Ulwan's opinion that in fostering and educating morals using the methods of habituation, example, advice, attention and supervision and punishment . And parents have taught their children about manners, honesty, being trustworthy, generous, independent and responsible.